Firm Productivity and Ethnic Wages - David C. Maré; Richard Fabling (Institute of Labor Economics (IZA), 2025)
We estimate relative wage discrimination for ethnic and migrant groups in New Zealand, using linked employer-employee and firm-level productivity data, and comparing each group's contribution to output with their share of their firm's wage bill. We find that wage discrimination is relatively favourable for European migrants and Asian/MELAA employees, and relatively unfavourable for M?ori, Pacific, and NZ-born European employees, with variation across NZ-born, recent migrants, and longer-term migrants. We present pooled and firm-fixed effects estimates of discrimination, highlighting distinct within-firm and between-firm patterns.
Keywords: J15; J30; J42; J71; 330; earnings; productivity; ethnicity